MODEL KOPERASI PESANTREN, KEPEMIMPINAN PENDIDIKAN, DAN KONTRIBUSINYA TERHADAP KEMANDIRIAN EKONOMI SANTRI - Annisa Ayu Lestari; Arsel Himma Azhar; Dina Amelia; Siswadi Siswadi (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
The economic independence of Islamic boarding schools has become an important issue amidst the demands of globalization and limited external funding. Cooperatives within these schools serve as one instrument for empowering students, yet in practice their management remains less than optimal and their contribution to students' economic independence is still limited. This study seeks to identify the models of Islamic boarding school cooperatives that have developed in Indonesia and to analyze how each model contributes to students' economic independence. A qualitative approach was employed using library research. Data were drawn from scientific journal articles, books, proceedings, and relevant official documents. Data collection was carried out through documentation study, while data analysis used content analysis with the stages of reduction, presentation, and conclusion drawing. The findings reveal three models of Islamic boarding school cooperatives: the traditional model in the form of a general store, the productive business diversification model, and the integrated sharia cooperative model. The contribution of cooperatives to students' economic independence includes meeting basic needs at affordable prices, entrepreneurship education, improving managerial skills, and internalizing Islamic economic values. Among the three models, the integrated sharia cooperative contributes the most, followed by the diversification model, and finally the traditional model. The success of cooperative development is strongly determined by the quality of visionary, transformational, and ecotheology-based leadership. From these findings, it can be concluded that transforming from a traditional model toward a more modern and integrated model is an essential prerequisite for Islamic boarding school cooperatives to truly function as a pillar of students' economic independence.